2020
DOI: 10.1002/pbc.28217
|View full text |Cite
|
Sign up to set email alerts
|

Parent recommendation to bank sperm among at‐risk adolescent and young adult males with cancer

Abstract: Background Adolescent and young adult (AYA) males newly diagnosed with cancer are often faced with making quick decisions about whether to cryopreserve (“bank”) sperm prior to treatment initiation. Given that parental influence is crucial among young patients, the present study examines the prevalence of and factors associated with parent recommendation to bank sperm. Procedure Parents of 13‐ to 21‐year‐old males newly diagnosed with cancer and at risk for infertility secondary to impending gonadotoxic treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Thus, in the context of a new cancer diagnosis, members of the family are affected and involved in making healthcare-related decisions. Along these lines, recent studies among male adolescents with cancer have identified parents, and particularly fathers, as key influencers in sperm banking decision making [ 15 , 16 , 17 ]. Due to their young age, adolescents’ future-oriented thinking may be developmentally limited, further highlighting the importance of family-centered research on the decision making experiences of this population [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the context of a new cancer diagnosis, members of the family are affected and involved in making healthcare-related decisions. Along these lines, recent studies among male adolescents with cancer have identified parents, and particularly fathers, as key influencers in sperm banking decision making [ 15 , 16 , 17 ]. Due to their young age, adolescents’ future-oriented thinking may be developmentally limited, further highlighting the importance of family-centered research on the decision making experiences of this population [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mental health of male infertile patients should not be ignored, as mental health also has a serious impact on men. In Jessica S. Flynn's study (70), more than half of the 138 parents preferred their sons to freeze their sperm, as evidenced by parental social pressure (71). Many studies have suggested that depression is as common in infertile men as in infertile women (72)(73)(74)(75).…”
Section: Male Dimensionmentioning
confidence: 99%
“…Parents are often unaware of their child's future parenthood goals [24], withhold their own perspectives about FP [25], and frequently defer the FP decision to their son [26]. Given that AEAs are developmentally limited in their ability to engage in future-oriented thinking [27], research has shown that parents (especially fathers) play a key role in sperm banking decision-making [28][29][30]. Specifically, when parents encourage the use of FP, AEAs are more likely to attempt FP [29][30][31].…”
Section: Introductionmentioning
confidence: 99%